Development of a Digital Module for Kinematics Material Based on 3D Visual Animation through the MOOCS Platform to Improve Understanding of Concepts - Wijaya, M. Abdilah Hananta; Risdianto, Eko; Koto, Irwan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to develop a digital kinematics material module using 3D visual animation through the MOOCs platform to improve conceptual understanding in 37 students of class XI K.10 SMA Negeri 7 Kota Bengkulu. The method used in this study is Research and Development (R&D), with the ADDIE development model. The results of the study showed that in physics learning in class XI: (1) validation of media feasibility produced a score of 117 with a percentage of 93.60%; (2) the N-gain value obtained was 0.72; and (3) assessment of student responses to the media obtained a percentage of 84%, while the teacher's response reached 95%. Based on these findings, it is concluded that the digital module based on 3D visual animation through the MOOCs platform is very feasible to be used to improve students' conceptual understanding of kinematics material.